Combining biometrics and self-reports to better understand perceptions of source trustworthiness, expertise, and believability in HPV blog messaging - Laura Crosswell (Health Literacy and Communication Open, 2025)
Background The recent surge in user-generated, online activity shifts the dynamics driving public trust in healthcare information. As more voices gain social capital, consumers struggle to identify reliable sources of information. Our new media environment and redefined concepts of expert credentials have consequently complicated the nature of “credibility” and trust in public health messaging.Aims This study aims to address gaps in both the literature and data collection techniques that inform the current body of HPV-related health communication scholarship. Specifically, the following work combines different measures of message processing (comparing implicit gaze behaviors with explicit self-reports) to examine the effect of source credentials on audience perception of source trustworthiness/expertise, content credibility, and message believability regarding HPV health information.Methods I examine the psychophysiological impact of source credentials on audience reception of HPV-related blog posts. Using eye tracking technology and post-test surveys, I look at how different source stimuli (“actress,” “blogger,” and “doctor”) impact viewer processing of HPV health messaging. I conducted a between-group comparison of implicit/explicit reactions among 144 participants, examining viewer fixations on source credentials in relation to perceived trustworthiness, message believability, and content credibility.Results Key findings show that eye fixations on source credentials based on source stimuli significantly predicts perceptions of source trustworthiness. More specifically, results demonstrated gaze fixation and trust is moderated by source credentials; more attention is predictive of more trust when the source is trustworthy (e.g., a doctor) but more attention is predictive of less trust when the source is not trustworthy (e.g., an actress). Message believability in turn positively influences vaccination intentions. Though key findings contrast with what was anticipated based on our evolving media environment, they do inform practice-based strategies.Discussion Findings presented throughout this research highlight the importance of strategically presenting source credentials in online health communication to enhance public trust. Featuring medical experts, pairing nonexpert sources with credible endorsements, and crafting clear, evidence-based messages may improve perceived trustworthiness and encourage health-promoting behaviors, such as HPV vaccination uptake. However, further work in this area is needed to help clarify the relationship between eye fixation and perceived trust in information.